The effectiveness of cognitive-behavioral hypnotherapy on distress tolerance and aggression in women with premenstrual dysphoria - Ahmadi Malayeri, Golmehr; Rahmani, Mohammad Ali; Pourasghar Arabi, Mehdi (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The current study was conducted with the aim of cognitive-behavioral hypnotherapy on distress tolerance and aggression in women suffering from premenstrual dysphoria. Method: The current study is a quasi-experimental type in which a pre-test-post-test design was conducted with a control group with measurement at the baseline after the intervention and a 3-month follow-up with the control group. 30 women aged 25 to 40 with a diagnosis of premenstrual boredom disorder who referred to psychological counseling centers in Sari city in 2019 were selected and randomly assigned to the experimental group (cognitive-behavioral hypnotherapy n=15) and (control n=15). were assigned All participants completed the demographic questionnaire, distress tolerance of Simmons and Gaher (2005) and aggression of Buss and Perry (1992), in three stages. The intervention sessions were conducted face-to-face in compliance with health protocols. Hypotheses related to the effectiveness of the research intervention were analyzed using multivariate covariance analysis and Lametrics post hoc test and using SPSS-19 software. Results: The results of the present study showed that there is no significant difference between the two groups in the pre-test stage of distress tolerance and aggression, which indicates the homogeneity of the two research groups in the pre-test stage, but there is a significant difference between the two groups in the post-test and follow-up stages. Which can indicate the effectiveness of the intervention on the mentioned variables and also the stability of the effectiveness in the follow-up phase. Conclusion: Considering the effectiveness of cognitive-behavioral hypnotherapy, this treatment should be prioritized.